2016
DOI: 10.2174/1389557516666160624124127
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Natural Product Gentiopicroside - a Secoiridoid Compound

Abstract: Gentiopicroside is a secoiridoid compound isolated from Gentiana lutea which is called Qin Jiao in Chinese. It is one of the most common herbal medicines used in China. In this article, we review the pharmacological and biological activity (antiviral, anti-inflammatory, analgesia, antihepatotoxic and choleretic), as well as biotransformation of the gentiopicroside. In addition, attempt towards the total synthesis of gentiopicroside is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Several previous studies have demonstrated that GL root extract contains various physiologically beneficial bioactive compounds [ 17 , 18 ]. To identify the bioactive constituent(s) that are responsible for the antiadipogenic effects of GL root extract, we performed fractionation of a 30% ethanol extract of GL root ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have demonstrated that GL root extract contains various physiologically beneficial bioactive compounds [ 17 , 18 ]. To identify the bioactive constituent(s) that are responsible for the antiadipogenic effects of GL root extract, we performed fractionation of a 30% ethanol extract of GL root ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…been used from ancient times in China. GPS, a water-soluble ingredient in GM has anti-inflammatory and hepatoprotective effects (Mirzaee et al, 2017;Wu et al, 2017). Previously, we reported GPS could reverse ethanol-induced liver steatosis and drug-induced liver injury (Lian et al, 2010b;Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As gentiopicroside is the major active compound of traditional Chinese oral decoction‐Longdan xiegan decoction, gentiopicroside was oral administration once a day in the present work. According to pharmacokinetic parameters of gentiopicroside (Liu, Liu, Dai, & Ma, 2018; Lu, Lin, & Tsai, 2014; Wu et al, 2017) and referring to published work, dose of gentiopicroside was set at 20 mg/kg, which equaled to 222 mg per day for 70 kg adults. Although as reported that gentiopicroside at oral 40 mg/kg for mice (equaled 28 mg/kg for rats) showed no toxicity in the liver (Li et al, 2018; Yang et al, 2020), however, there are few reports on the toxicity experiments, which limits the safety evaluation of gentiopicroside.…”
Section: Discussionmentioning
confidence: 99%